2006
DOI: 10.1002/ejoc.200600440
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Glycosylations Using (R)‐ or (S)‐(Ethoxycarbonyl)benzyl Chiral Auxiliaries at C‐2 of Glycopyranosyl Donors

Abstract: The stereoselective introduction of a glycosidic bond presents the greatest challenge to complex oligosaccharide synthesis. Important developments such as automated polymer‐supported oligosaccharide synthesis will not realize their full potential until this problem is addressed. In this paper, a novel approach for stereoselective glycosylations is described whereby a chiral auxiliary at C‐2 of a glycosyl donor controls the anomeric outcome of a glycosylation. It was found that participation of an (S)‐ethoxycar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 40 publications
0
43
0
Order By: Relevance
“…Boons and co-workers have noted a similar effect when using glycosyl donors bearing chiral auxiliaries. [42,49] Specifically, if an ester or carbonate protecting group was used at the O3 position, then stereoselectivities were much higher than when using an ether protecting group at O3. They proposed that an S N 2-like mechanism could be favoured by either 1) the use of protecting groups that would destabilise an oxacarbenium ion intermediate or by 2) modifying the auxiliary to increase the stability of the sulfonium ion.…”
Section: Wwwchemeurjorgmentioning
confidence: 96%
“…Boons and co-workers have noted a similar effect when using glycosyl donors bearing chiral auxiliaries. [42,49] Specifically, if an ester or carbonate protecting group was used at the O3 position, then stereoselectivities were much higher than when using an ether protecting group at O3. They proposed that an S N 2-like mechanism could be favoured by either 1) the use of protecting groups that would destabilise an oxacarbenium ion intermediate or by 2) modifying the auxiliary to increase the stability of the sulfonium ion.…”
Section: Wwwchemeurjorgmentioning
confidence: 96%
“…For instance, while Boons et al found that the glycosidation of sulfonium salts results in excellent S N 2-like stereoselectivity, 17,19,39,40 several research groups have conversely encountered poor or unanticipated anomeric selectivities when dealing with these key intermediates. Yoshida et al found that both the α- and β-sulfonium species fail to undergo the anticipated inversion.…”
mentioning
confidence: 99%
“…7071 Thus, the S -configured donors 29 were found to afford α-glucosides 30 selectively, while the R -configured diastereomers 31 gave the β-glucosides 32 selectively (Scheme 4). These results were rationalized in terms of participation by the ethoxycarbonylbenzyl group with preferential formation of trans- and cis -decalin-like intermediates 33 and 34 for the S - and R -series, respectively, so as to accommodate the phenyl group in an equatorial position (Scheme 4).…”
Section: Discussionmentioning
confidence: 99%
“…Computations were advanced in support of this hypothesis. 71 In the S -series the use of an ester protecting group for O3 ( 29 , R = Ac, Bz or Alloc) was essential for α-selectivity as ether protection at that position ( 29 , R = allyl) gave less selective and even β-selective glucosylation depending on the acceptor employed. In the R -series the dependence of selectivity on the 3- O -protecting group was less marked ( 31 , R = Allyl, Ac, Bz or Alloc).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation